Cyclic nucleotide phosphodiesterase‐1C (PDE1C) drives cell proliferation, migration and invasion in glioblastoma multiforme cells in vitro. Issue 3 (25th January 2015) - Rowther, Farjana B.; Wei, Weinbin; Dawson, Timothy P.; Ashton, Katherine; Singh, Anushree; Madiesse‐Timchou, Mylene P.; Thomas, D.G.T.; Darling, John L.; Warr, Tracy
Abstract : Cyclic nucleotides (cAMP & cGMP) are critical intracellular second messengers involved in the transduction of a diverse array of stimuli and their catabolism is mediated by phosphodiesterases (PDEs). We previously detected focal genomic amplification of PDE1C in >90 glioblastoma multiforme (GBM) cells suggesting a potential as a novel therapeutic target in these cells. In this report, we show that genomic gain of PDE1C was associated with increased expression in low passage GBM‐derived cell cultures. We demonstrate that PDE1C is essential in driving cell proliferation, migration and invasion in GBM cultures since silencing of this gene significantly mitigates these functions. We also define the mechanistic basis of this functional effect through whole genome expression analysis by identifying down‐stream gene effectors of PDE1C which are involved in cell cycle and cell adhesion regulation. In addition, we also demonstrate that Vinpocetine, a general PDE1 inhibitor, can also attenuate proliferation with no effect on invasion/migration. Up‐regulation of at least one of this gene set ( IL8, CXCL2, FOSB, NFE2L3, SUB1, SORBS2, WNT5A, and MMP1 ) in TCGA GBM cohorts is associated with worse outcome and PDE1C silencing down‐regulated their expression, thus also indicating potential to influence patient survival. Therefore we conclude that proliferation, migration, and invasion of GBM cells could also be regulated downstream of PDE1C . © 2015 Wiley Periodicals, Inc.